Transcriptional regulation of cellobiose utilization by PRD-domain containing Sigma54-dependent transcriptional activator (CelR) and catabolite control protein A (CcpA) in Bacillus thuringiensis - Zhang, Liangwei; Xu, Hong; Cheng, Haijian; Song, Fuping; Zhang, Jie; Peng, Qi (Frontiers in Microbiology, 2024)
Cellobiose, a β-1,4-linked glucose dimer, is a major cellodextrin resulting from the enzymatic hydrolysis of cellulose. It is a major source of carbon for soil bacteria. In bacteria, the phosphoenolpyruvate (PEP): carbohydrate phosphotransferase system (PTS), encoded by the cel operon, is responsible for the transport and utilization of cellobiose. In this study, we analyzed the transcription and regulation of the cel operon in Bacillus thuringiensis (Bt). The cel operon is composed of five genes forming one transcription unit. β-Galactosidase assays revealed that cel operon transcription is induced by cellobiose, controlled by Sigma54, and positively regulated by CelR. The HTH-AAA + domain of CelR recognized and specifically bound to three possible binding sites in the celA promoter region. CelR contains two PTS regulation domains (PRD1 and PRD2), which are separated by two PTS-like domains-the mannose transporter enzyme IIA component domain (EIIA Man ) and the galactitol transporter enzyme IIB component domain (EIIB Gat ). Mutations of His-546 on the EIIA Man domain and Cys-682 on the EIIB Gat domain resulted in decreased transcription of the cel operon, and mutations of His-839 on PRD2 increased transcription of the cel operon. Glucose repressed the transcription of the cel operon and catabolite control protein A (CcpA) positively regulated this process by bindingthe cel promoter. In the celABCDE and celR mutants, PTS activities were decreased, and cellobiose utilization was abolished, suggesting that the cel operon is essential for cellobiose utilization. Bt has been widely used as a biological pesticide. The metabolic properties of Bt are critical for fermentation. Nutrient utilization is also essential for the environmental adaptation of Bt. Glucose is the preferred energy source for many bacteria, and the presence of the phosphotransferase system allows bacteria to utilize other sugars in addition to glucose. Cellobiose utilization pathways have been of particular interest owing to their potential for developing alternative energy sources for bacteria. The data presented in this study improve our understanding of the transcription patterns of cel gene clusters. This will further help us to better understand how cellobiose is utilized for bacterial growth.